Fasting, crowding and temperature effects on the cardiac activity of European seabass during ice-slurry slaughtering procedure - E. Hoyo-Alvarez; M.J. Cabrera-Álvarez; P. Arechavala-Lopez; A. Roque (Aquaculture Reports)
Aquaculture production continues to expand rapidly, highlighting the need to improve welfare standards during harvesting procedures. Pre-slaughter operations such as fasting and crowding, along with slaughter procedures, represent critical points with significant welfare implications. In this study, the effects of pre-slaughter protocols and seasonal temperature on cardiac responses during slaughter in European seabass (Dicentrarchus labrax) were evaluated. To monitor cardiac activity, biologgers were surgically implanted in pre-adult seabass subjected to fasting periods and crowding protocols, followed by slaughter in ice slurry or ikejime (a rapid killing method involving brain destruction) at different seasonal temperatures (summer and winter). Results revealed that fasting significantly reduced the time to loss of cardiac function during ice slurry slaughter, particularly under warmer conditions, as fasted individuals lost cardiac activity 14 min earlier than controls, likely due to energy depletion. Crowding elevated heart rate during ice slurry slaughter, counteracting the expected bradycardic response to ice, particularly in summer, where crowded fish lost cardiac signal 11 min earlier than controls. Seasonal variation in water temperature strongly influenced physiological outcomes: winter trials resulted in markedly prolonged cardiac activity during ice exposure, with cessation of cardiac activity times up to 219 min in fasted fish, compared to 32 min in summer. Additionally, crowded fish in summer showed sustained high heart rates and faster cardiac cesssation, indicating acute stress despite shortened duration. These findings suggest that pre-slaughter stressors and environmental conditions interact to shape welfare outcomes. While fasting may improve slaughter efficiency during summer, crowding under high temperatures poses a welfare concern. From a welfare-oriented perspective, minimising crowding and tailoring fasting protocols to seasonal conditions are recommended to improve slaughter efficiency and reduce stress in seabass aquaculture.